A novel and efficient route for aryl ketones generation over Co3O4/Ag@C3N4 photocatalyst. (2nd November 2019) - Chen, Peng; Liu, Fan; Chen, Sheng; Guo, Jun-Kang; Shen, Sheng; Chen, Lang; Au, Chak-Tong; Yin, Shuang-Feng
Graphical abstract: Highlights: Porous C3 N4 nanorods decorated with spatially separated Ag and Co3 O4 were prepared. The structure is benefit for light absorption and separation of charge carriers. Benzophenone can efficiently generate over the Co3 O4 /Ag@C3 N4 photocatalyst. It is an efficient method for the generation of benzophenone-based intermediates. Abstract: Aryl ketones are ubiquitous structural motifs in organic synthesis. Nonetheless, the traditional methods for their generation are often costly and not environment-friendly. Herein we report a novel and efficient route for the preparation of aryl ketones by photocatalysis at mild conditions. Porous C3 N4 nanorods decorated with spatially separated Ag and Co3 O4 nanoparticles on the interior and exterior surface of C3 N4 hollow sphere (Co3 O4 /Ag@C3 N4 ) fabricated by a facile method of supramolecular self-assembly. Using this porous material as photocatalyst and O2 as oxidant, aryl ketones could efficiently generate (with a yield up to 75.7% and selectivity to 97%) via toluene and halobenzene under visible-light irradiation at room temperature. The present study not only provides an inexpensive strategy for aryl ketones generation but also an effective tactic for activation of sp 3 CH bonds under mild conditions.